Poly (ADP-ribose) polymerase inhibitor therapy and mechanisms of resistance in epithelial ovarian cancer - Kulkarni, Sanat; Gajjar, Ketankumar; Madhusudan, Srinivasan (Frontiers in Oncology, 2024)
Advanced epithelial ovarian cancer is the commonest cause of gynaecological cancer deaths. First-line treatment for advanced disease includes a combination of platinumtaxane chemotherapy (post-operatively or peri-operatively) and maximal debulking surgery whenever feasible. Initial response rate to chemotherapy is high (up to 80%) but most patients will develop recurrence (approximately 70-90%) and succumb to the disease. Recently, poly-ADP-ribose polymerase (PARP) inhibition (by drugs such as Olaparib, Niraparib or Rucaparib) directed synthetic lethality approach in BRCA germline mutant or platinum sensitive disease has generated real hope for patients.PARP inhibitor (PARPi) maintenance therapy can prolong survival but therapeutic response is not sustained due to intrinsic or acquire secondary resistance to PARPi therapy. Reversion of BRCA1/2 mutation can lead to clinical PARPi resistance in BRCA-germline mutated ovarian cancer. However, in the more common platinum sensitive sporadic HGSOC, the clinical mechanisms of development of PARPi resistance remains to be defined. Here we provide a comprehensive review of the current status of PARPi and the mechanisms of resistance to therapy.